Whether the start time of elective lung surgery impacts perioperative outcomes and cost? - A-Lai, Gu-Ha; Hu, Jian-Rong; Xu, Zhi-Jie; Yao, Peng; Zhong, Xia; Wang, Yu-Cheng; Lin, Yi-Dan (Frontiers in Surgery, 2022)
Background Fatigue and the long work hours of surgeons have attracted increasing concern in recent years. We aimed to explore whether starting time was associated with perioperative outcomes and cost for elective lung surgery. Methods A retrospective study was conducted on elective lung surgery patients at a high surgery-volume center between September 2019 and November 2019. Patients were divided into the “early start group” if the surgery start time was before 4 post meridiem (pm), while the “late start group” was defined as surgery started after 4 pm. Perioperative outcomes and total hospital costs were compared between the two groups. In addition, multivariable logistic regression analysis was performed to identify whether start time was a risk factor for postoperative hospital duration, total hospital cost and length of operation time. Results A total of 398 patients were finally enrolled for analysis in this study. Of all the cases, 295 patients were divided into the early start group, while 103 patients belonged to the late start group. Baseline characteristics were all comparable between the two groups. Concerning Regarding outcomes, there were no differences in postoperative hospital duration, operation time, complication incidence or and other outcomes, while the total hospital cost tended to be different but still not significantly different without statistical significance (P = 0.07). In multivariable logistic regression analysis, surgery starting late was still not found to be a risk factor for long postoperative hospital duration, high hospital cost and long surgery time. Conclusion In elective lung surgery, perioperative outcomes and costs were similar between the early- and late-start groups, and it was not necessary to worry about the surgery order for these patients.